Pengembangan Math Pocket Book Tipe Higher Order Thinking Skills (HOTS) sebagai Media Pembelajaran Matematika Siswa Kelas VII SMP - Amin, Salsa Bila Rona; Ammamiarihta (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
This study aims to develop a Mathematics learning media in the form of a Math Pocket Book with a Higher Order Thinking Skills (HOTS) approach that is valid, practical, and effective, with a focus on enhancing student motivation and creating an engaging learning environment. The research was conducted at SMPN 3 Medan during the academic year 2023/2024, using the Research and Development (R&D) method and following the 4-D model (Define, Design, Development, and Disseminate) developed by Thiagarajan. The validation results of the Math Pocket Book by validators showed a validity rate of 86.67%, indicating excellent validity. Furthermore, in a small-scale trial involving 20 students from class VIII-H, an N-Gain score of 62.49% was obtained in comparison between pre-tests and post-tests, demonstrating a sufficient level of effectiveness for use as a Mathematics learning media. Additionally, based on teacher responses to the questionnaire, the book was considered highly practical, with a practicality rating of 96.47%. According to student responses in the questionnaire, the book was also deemed highly practical, with a rating of 82.59%. Based on the results and discussions of the research conducted, the Math Pocket Book with a Higher Order Thinking Skills (HOTS) approach is considered to meet the standards of validity, effectiveness, and practicality required for use as a Mathematics learning media for 7th-grade junior high school students.